(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1852)
The Rev. JEneas M’Donald Dawson of Dunfermline presented three silver brooches, found in the ruins of the ancient’ church of Middelbie, Annandale, Dumfriesshire, 1849. Several other brooches are also exhibited.